Hubungan Antara Faktor Lingkungan Usaha Dengan Keberhasilan Kinerja Koperasi - Khoiriyah C, Nailatul (Tasharruf : Journal of Islamic Economics and Business, 2020)
The research purposes are: 1) To describe the farmer social economic conditions in research area, 2) Describe the farmer motivation on this technology.3) Describe the farmer participations on this technology. 4) To analyze the relationship between social economic factors with farmer motivation on this technology.5) To analyze the relationship between social economic factors with farmer participations on this technology. This research is explanatory research, while the method of research is survey. In this research used by 20 samples who taken using method of simple random sampling. Data analysed by using descriptive analysis and Rank Spearman correlation analysis. The research results are:1) Social Economic condition of farmer in research area include in medium category.2) Farmer Motivations on this technology include high category.3) Farmer participation on this technology include in high category. 4) There are no correlations between social economic factors with farmer motivations on technology. It caused of farmer motivation in high category and social economic factors in statistic analysis are homogeny. 5) There are correlations between social economic factors with the farmer participation. Suggestion that extended based on the result from this research was: 1) Farmer motivation on this technology is high, it needs to be maintain, in order farmer always motivated to participant application this technology. So it will increase their production and income. 2) Farmer participation on this technology is good. But it needs to be increase especially at planning with activated farmer in each government program which related with plantation technology development.